Progerinin, an optimized progerin-lamin A binding inhibitor, ameliorates premature senescence phenotypes of Hutchinson-Gilford progeria syndrome - So-mi Kang (Nature Portfolio, 2021)
Kang, Park and colleagues develop and demonstrate the effects of a new drug candidate for treatment of Hutchinson-Gilford progeria syndrome pathologies. Progerinin extends the life span of mice used to model this disease and induces histological and physiological improvements.